Perceptions toward considering nursing as a career choice among secondary school students = Persepsi tentang mempertimbangkan keperawatan sebagai pilihan karir pada siswa sekolah sekunder - Che Hasan, Muhammad Kamil; Jusoh, Nurul Syafiqah; Abdul Hamid, Siti Hazariah; Nurumal, Mohd. Said (Faculty of Nursing Universitas Indonesia, 2020)
Demand for a nursing career in Malaysia has increased, although it has not been a popular course of choice among students. Understanding the perceptions of students about nursing may help identify any misconception toward the profession and their consideration to choose nursing as a career. This study aimed to identify the perceptions of secondary school students about nursing and their potential interest in joining a nursing career. A cross-sectional study using convenience sampling was conducted among 155 students by administering a High School Students Self-Administered Questionnaire from three selected secondary schools in Kuantan, Pahang Malaysia. Overall, the respondents positively perceived the nursing profession, although several parts were viewed negatively. Despite having a positive notion about nursing, only 18.1% of the respondents were interested to select nursing as their career and a majority of them were women. In conclusion, no significant difference in perceptions about nursing and consideration to choose nursing as a career was found. Nevertheless, the image of nurses and a nursing career need to be improved in the eye of students and societies. In addition, the students were not aware of the benefits of nursing with several misconceptions of genders and doctor’s aid. Overall, the status of nursing in Malaysia should be enhanced to make it a valuable career. ******************************************************************************* Permintaan untuk karir keperawatan di Malaysia mengalami peningkatan, meskipun belum menjadi pilihan populer di kalangan siswa. Pemahaman mengenai persepsi siswa tentang keperawatan dapat membantu mengidentifikasi kesalahpahaman terhadap profesi dan pertimbangan mereka untuk memilih keperawatan sebagai karier. Penelitian ini bertujuan untuk mengidentifikasi persepsi siswa sekolah menengah tentang keperawatan dan potensi minat mereka untuk memilih karir keperawatan. Sebuah studi cross-sectional menggunakan convenience sampling dilakukan pada 155 siswa dengan High School Students Self-Administered Questionnaire dari tiga sekolah menengah di Kuantan, Pahang Malaysia. Secara keseluruhan, responden memandang positif profesi keperawatan, namun beberapa bagian dipandang negatif. Meskipun memiliki gagasan positif tentang keperawatan, hanya 18,1% dari responden tertarik untuk memilih keperawatan sebagai karir mereka dan mayoritas dari mereka adalah perempuan. Kesimpulannya, tidak ada perbedaan signifikan dalam persepsi tentang keperawatan dan pertimbangan untuk memilih keperawatan sebagai karier. Namun demikian, citra perawat dan karier keperawatan perlu ditingkatkan di mata siswa dan masyarakat. Selain itu, siswa tidak menyadari manfaat keperawatan dengan beberapa kesalahpahaman tentang gender dan bantuan dokter. Secara keseluruhan, status keperawatan di Malaysia harus ditingkatkan untuk menjadikannya karier yang berharga.